2000
DOI: 10.1007/s001340000762
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of airway accidents in intubated ICU patients

Abstract: We noted a change of the pattern of airway accidents. We noted an increasing trend in the incidence of blocked tracheal tubes, associated with an increased duration of heat and moisture exchanger-filters use. We also noted that the incidence of tracheostomy tube accidents was similar to that of ETT accidents in the current study, unlike the earlier study where tracheostomy tube accidents were more frequent than ETT accidents. This was due to the elimination of tracheostomy tube displacements during the later s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
4
12
2
Order By: Relevance
“…These authors [8,9] studied patients who were randomly assigned to different types of airway humidifiers, whereas we performed a matched-pair study controlled for ETT diameter, days of mechanical ventilation, SAPS II, and fluid balance. Our patients were assigned to HH or HME according to clinical needs and common recommendations [3,[12][13][14][15]. This clinical selection of the type of humidifier carried out in our study, according to the main respiratory diagnosis and secretion management needs, instead of randomization performed in those studies, may explain the differences found in the ETT resistance over time when comparing our study with those previously published.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These authors [8,9] studied patients who were randomly assigned to different types of airway humidifiers, whereas we performed a matched-pair study controlled for ETT diameter, days of mechanical ventilation, SAPS II, and fluid balance. Our patients were assigned to HH or HME according to clinical needs and common recommendations [3,[12][13][14][15]. This clinical selection of the type of humidifier carried out in our study, according to the main respiratory diagnosis and secretion management needs, instead of randomization performed in those studies, may explain the differences found in the ETT resistance over time when comparing our study with those previously published.…”
Section: Discussioncontrasting
confidence: 51%
“…Current data show no preferential performance of either HME or HH devices in mechanically ventilated patients concerning the incidence of ventilator-associated pneumonia, mortality, or morbidity [10,11]. The type of humidification used during routine mechanical ventilation should be chosen on the basis of a patient's underlying disease [12,13], respiratory mechanics [14], quality of respiratory secretions [3,15], the mechanical ventilation settings [16], and ambient and patient temperature [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The main finding of those studies was that the rates of accidents were low and the most common forms of accidents was unplanned extubation or displacement of the tracheal tube. Taken together there were a total of 41 incidents of tracheal tube displacement in 7978 patients (0.51%) over 15,628 days (0.26%).…”
Section: Introductionmentioning
confidence: 99%
“…Immediate complications include haemorrhage and loss of the airway, with short-term complications including blockage or complete or partial tracheostomy tube displacement. Long-term complications include tracheomalacia, tracheal stenosis or problems relating to the stoma itself [3][4][5][6]. A variety of artificial airway devices can be inserted into tracheostomy or laryngectomy stomas and these may become blocked or displaced, leading to significant patient harm.…”
mentioning
confidence: 99%
“…Following a cluster of serious untoward incidents involving hospitalised 'neck breathers' in the North West of England, similar critical incidents reported to the UK National Patient Safety Agency (NPSA) were examined and recurrent themes were identified [9,10], evident in similar publications [4,5,11,12,[23][24][25][26][27]. It was clear that simple, clear and authoritative guidelines were urgently required, similar in structure to previous DAS algorithms and Resuscitation Council (UK) guidelines [28].…”
mentioning
confidence: 99%